2022
DOI: 10.3390/diagnostics12123005
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Radiomics Nomogram for Predicting Prostate Cancer with Gray-Zone Prostate-Specific Antigen Levels to Reduce Unnecessary Biopsies

Abstract: Objective: The aim of this study was to establish a predictive nomogram for predicting prostate cancer (PCa) in patients with gray-zone prostate-specific antigen (PSA) levels (4–10.0 ng/mL) based on radiomics and other traditional clinical parameters. Methods: In all, 274 patients with gray-zone PSA levels were included in this retrospective study. They were randomly divided into training and validation sets (n = 191 and 83, respectively). Data on the clinical risk factors related to PCa with gray-zone PSA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Radiomics features offer the advantages of being an objective and quantitative tool. In our study, the radiomics model exhibited the best performance in both the training and testing groups, with an AUC of 0.932 and 0.922, respectively, which is consistent with the results of the two previous studies 24 , 25 , with an AUC of 0.844 and 0.941, respectively. The other previous study 26 employed radiomics features extracted from 2D segmentations to predict the risk of PCa in men with PSA levels of 4–10 ng/mL.…”
Section: Discussionsupporting
confidence: 91%
“…Radiomics features offer the advantages of being an objective and quantitative tool. In our study, the radiomics model exhibited the best performance in both the training and testing groups, with an AUC of 0.932 and 0.922, respectively, which is consistent with the results of the two previous studies 24 , 25 , with an AUC of 0.844 and 0.941, respectively. The other previous study 26 employed radiomics features extracted from 2D segmentations to predict the risk of PCa in men with PSA levels of 4–10 ng/mL.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors have recently tried to develop and validate nomograms for the prediction of CS PCa. Nevertheless, these nomograms focused on a specific population with grey-zone PSA level (4-10 ng/mL) or PI-RADS 3 lesions [29,30]. Instead of targeting our work only on a pre-specified category, we avoided this and superselected our population in order to obtain data from a real-life cohort and a radiomic tool that could be more generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the screening of csPCa becomes an important part of the treatment strategy (15). Studies have shown that approximately 75% of patients undergo unnecessary prostate biopsies based on PSA values only (16,17). Excessive biopsies lead to serious complications, such as urinary tract infections, pain, and hematuria (18).…”
Section: Discussionmentioning
confidence: 99%